Interactive 3D multimedia learning tools in biology / Chin Siaw Khim - Chin , Siaw Khim (2006)
An interactive 3D Multimedia Learning tool in Biology is an application system to assist users in the brand new learning style for biology. Combination of the virtual and multimedia in the system can bring out the clear explanation of processes and delivery the information. Besides that, the system enables users to interactive with the system to help them in the learning biology. The web-based application also encourage sharing knowledge through distance learning between the user. An interactive 3D Multimedia Learning tools in Biology mainly focus on Biology Cell topic with SPM syllabus. The target user for this system is mainly focus on PM students, but this system also suitable for educators, researchers and public user. Conclusion, this is the effectiveness application in the future education field.